Perbandingan Tingkat Kepatuhan Minum Obat pada Penderita Skizofrenia dengan Indeks Massa Tubuh Normal dengan Indeks Massa Tubuh Tidak Normal di RSUD Dr. Pirngadi Medan Tahun 2026 - Ritha Mariati Sembiring; Reinaldy Pangihutan Hutasoit; Yance Roberta Tobing; Karina Mutiarani Halawa; David Renaldy Tampubolon; Welni Ratna Sari Halawa (Institut Nalanda, 2026)
Schizophrenia is a chronic mental disorder that requires long-term antipsychotic therapy. Medication adherence plays an important role in treatment success but is often affected by drug side effects such as weight gain, which impacts Body Mass Index (BMI). Changes in BMI may influence patient motivation and adherence to treatment. This quantitative study used a cross-sectional design conducted at Dr. Pirngadi General Hospital Medan from January to February 2026. A total of 106 schizophrenia patients were selected using quota sampling. Medication adherence was measured using the Morisky Medication Adherence Scale-8 (MMAS-8), and BMI was calculated based on weight and height measurements. Data were analyzed using the Chi-Square test with a 95% confidence level. Most respondents had abnormal BMI (72 patients; 67.9%), and high medication adherence was found in 74 patients (69.8%). In the normal BMI group, most patients had high adherence (30 patients; 88.2%), while in the abnormal BMI group, high adherence was found in 44 patients (61.1%). Chi-Square analysis showed a significant relationship between BMI and medication adherence in schizophrenia patients (p=0.017).